The Gut Microbiota and Respiratory Diseases: New Evidence - Li Chunxi; Liu Haiyue; Lin Yanxia; Pan Jianbing; Su Jin (Journal of Immunology Research)
Human body surfaces, such as the skin, intestines, and respiratory and urogenital tracts, are colonized by a large number of microorganisms, including bacteria, fungi, and viruses, with the gut being the most densely and extensively colonized organ. The microbiome plays an essential role in immune system development and tissue homeostasis. Gut microbiota dysbiosis not only modulates the immune responses of the gastrointestinal (GI) tract but also impacts the immunity of distal organs, such as the lung, further affecting lung health and respiratory diseases. Here, we review the recent evidence of the correlations and underlying mechanisms of the relationship between the gut microbiota and common respiratory diseases, including asthma, chronic obstructive pulmonary disease (COPD), cystic fibrosis (CF), lung cancer, and respiratory infection, and probiotic development as a therapeutic intervention for these diseases.